RSI/WRMSD in the third decade after restructuring of banking: new associated factors? - Scopel, Juliana; Oliveira, Paulo Antonio Barros; Wehrmeister, Fernando César (Revista de Saúde Pública, 2012)
OBJECTIVE: To estimate the prevalence of cases suggestive of repetitive strain injury/work-related musculoskeletal disorders (RSI/WRMSD), three decades after restructuring of banking. METHODS: This was a cross-sectional study on 356 employees in 27 bank branches of public and private banks in Porto Alegre, Southern Brazil, between April and August 2009. After crude statistical analysis, adjustments were made using a Poisson regression model with robust variance and a three-level hierarchy that incorporated the design structure and adjustments for the clusters. The results were stratified according to the size of the bank branch and were dichotomized (>; 25; ≤ 25 employees). RESULTS: The prevalence of cases suggestive of RSI/WRMSD was lower among the men (PR = 0.62; 95%CI: 0.47-0.81). Workers aged 26 to 45 years (PR = 2.51; 95%CI 1.02;6.14) presented greater prevalence of this outcome. Individuals with postgraduate qualifications (PR = 0.45; 95%CI 0.22;0.90) and length of time in the job between 5.1 and 15 years (PR = 0.62; 95%CI 0.47;0.81) presented protection against RSI/WRMSD. On stratifying the analyses according to size, it was found that age, income and length of time in the job remained associated in branches with 25 employees or fewer, while in branches with more than 25 employees, sex and schooling level were associated with the outcome. CONCLUSIONS: The characteristics of importance in relation to bank employees who become ill due to rsi/wrmsd seem to be different today from those that were known historically. greater attention to organizing work and management strategies should be taken into consideration in drawing up illness prevention programs for banking work.